Molecular detection of Mycoplasma agalactiae and Mycoplasma capricolum in mastitic and non mastitic milk of goats by using Real Time Polymerase Chain Reaction - Jameel, Mohanad M.; Hasso, Saleem M. (The Iraqi Journal of Veterinary Medicine, 2018)
A total of 200 samples were collected from 100 goats from more than one regions within the three governorates (Sulaimani, Erbil and Duhok); all these samples were tested by California mastitis test and these showed the following results: 103 samples (51.50%) were negative in all governorates, 28(14.00%) were trace, 35(17.50%) were (+) mark and 34(17.00%) were (++) mark. Clinical mastitis was observed on 93 out of 200 half udder of goats, in the three governorates; 37(18.5%) were acute mastitis, 27(13.5%) were sub acute mastitis and 19(9.5%) were Chronic mastitis. Examination of extracted DNA by Real Time Polymerase Chain Reaction out of 200 DNA extracted from milk samples of goats only 10 (5.00%) were positive for Mycoplasma agalactiae in the three governorates, 8(80%) from mastatic milk samples and 2 (20%) from non mastatic milk samples in result of M. agalactiae. For Mycoplasma capricolum 6 (3.00%) were positive and all were from mastatic milk.